RATIONALITY BEHIND AYURVEDA COMPOUND FORMULATIONS- A BIRDS EYE VIEW - Saini, *Malvika; chaudhary, Anubha; Garg, Naveen kumar; Jaiswal, Mohan Lal; Kotecha, Mita (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda is Indian heritage system of medicine gifted by ancient Acharya. It provides scientific approach for dealing human health issues with tools of nature like herbs, minerals, metals etc. It states that every substance in the universe can be applied as medicine with the help of Yukti or logical approach of physicians. In present era, whole world is looking towards Ayurveda for its novel natural healing modalities to get relief from their ailments whether physical or mental. Hence here is the need for development of more numbers of Ayurveda formulations to overcome the different health hazard. Moreover invention of more formulations for newly developed diseases like cancer, AIDs, dengue etc. is also needed. But these herbal preparations also face problems like adulteration, non-availability in a particular area or extinction of herbs due to excessive use of a particular herb. On this background present study was undertaken to analyse the fundamental rationality behind Ayurveda formulations mentioned in various ancient transcripts. Literary data regarding evolving a formulation was scrutinized with examples of important formulations mentioned in various texts. This study results out that for developing a particular formulation, factors like availability, palatability, potency, safety, efficacy etc. should be considered.